Math, asked by kk1000, 2 months ago

check the differentiability of f(x) in [-2,2]
if f(x) is (see attachment). ​

Attachments:

Answers

Answered by shadowsabers03
8

The function f(x) in [-2, 2] is defined as,

\small\text{$\longrightarrow f(x)=\left\{\begin{array}{lr}\left(\cos\left(\dfrac{\pi}{2}\right)\right)\big(|x|-\{x\}\big),&x<1\\\\\{x\}\,\sqrt{4x^2-12x+9},&x\geq1\end{array}\right.$}

Including the interval [-2, 2] in the definition,

\small\text{$\longrightarrow f(x)=\left\{\begin{array}{lr}\left(\cos\left(\dfrac{\pi}{2}\right)\right)\big(|x|-\{x\}\big),&-2\leq x<1\\\\\{x\}\,\sqrt{4x^2-12x+9},&1\leq x\leq2\end{array}\right.$}

Since \small\text{$\cos\left(\dfrac{\pi}{2}\right)=0,$}

\small\text{$\longrightarrow f(x)=\left\{\begin{array}{lr}0,&-2\leq x<1\\\\\{x\}\sqrt{4x^2-12x+9},&1\leq x\leq2\end{array}\right.$}

We see that,

\small\text{$\longrightarrow\sqrt{4x^2-12x+9}=\sqrt{(2x)^2-2\cdot2x\cdot3+3^2}$}

\small\text{$\longrightarrow\sqrt{4x^2-12x+9}=\sqrt{(2x-3)^2}$}

\small\text{$\longrightarrow\sqrt{4x^2-12x+9}=|2x-3|$}

\small\text{$\longrightarrow\sqrt{4x^2-12x+9}=\left\{\begin{array}{lr}3-2x,&x\leq\dfrac{3}{2}\\\\2x-3,&x\geq\dfrac{3}{2}\end{array}\right.$}

Then, taking {x} = x - [x] also, we get,

\small\text{$\longrightarrow f(x)=\left\{\begin{array}{lr}0,&-2\leq x<1\\\\\big(x-[x]\big)(3-2x),&1\leq x\leq\dfrac{3}{2}\\\\\big(x-[x]\big)(2x-3),&\dfrac{3}{2}\leq x\leq2\end{array}\right.$}

Since [x] = 1 for 1 ≤ x < 2 and [x] = 2 for x = 2, the definition becomes,

\small\text{$\longrightarrow f(x)=\left\{\begin{array}{lr}0,&amp;-2\leq x&lt;1\\\\(x-1)(3-2x),&amp;1\leq x\leq\dfrac{3}{2}\\\\(x-1)(2x-3),&amp;\dfrac{3}{2}\leq x&lt;2\\\\(x-2)(2x-3),&amp;x=2\end{array}\right.$}

We see f(x) = 0 at x = 2.

\small\text{$\longrightarrow f(x)=\left\{\begin{array}{lr}0,&amp;-2\leq x&lt;1\\\\-2x^2+5x-3,&amp;1\leq x\leq\dfrac{3}{2}\\\\2x^2-5x+3,&amp;\dfrac{3}{2}\leq x&lt;2\\\\0,&amp;x=2\end{array}\right.$}

Now the derivative is,

\small\text{$\longrightarrow f'(x)=\left\{\begin{array}{lr}0,&amp;-2\leq x&lt;1\\\\-4x+5,&amp;1\leq x\leq\dfrac{3}{2}\\\\4x-5,&amp;\dfrac{3}{2}\leq x&lt;2\\\\0,&amp;x=2\end{array}\right.$}

We see the following.

  • \small\text{$\displaystyle\lim_{x\to1^-}f'(x)=0\neq1=\lim_{x\to1^+}f'(x)$}
  • \small\text{$\displaystyle\lim_{x\to\frac{3}{2}^-}f'(x)=-1\neq1=\lim_{x\to\frac{3}{2}^+}f'(x)$}
  • \small\text{$\displaystyle\lim_{x\to2^-}f'(x)=3\neq0=\lim_{x\to2^+}f'(x)$}

It means f(x) is not differentiable at points x = 1, x = 3/2, x = 2.

Similar questions